2016
DOI: 10.1089/gtmb.2016.0020
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cell Cyle Regulators Cyclin D1, CDK4, and p53 in Knee Osteoarthritis

Abstract: Expression of the Cyclin D1, CDK4, and p53 genes are correlated with the disease grades of KOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…As a function of the DNA damage magnitude, p53 may orchestrate homeostatic activities or dysfunctional responses, such as irreversible cell cycle arrest, senescence, or apoptosis [ 27 ] ( Figure 1 ). A recent report explored the correlation of gene and protein expression of cyclin D1, cyclin-dependent kinase 4, and p53 in cartilage derived from a large cohort of patients and healthy controls and showed that cyclin D1 and cyclin-dependent kinase 4 are negatively correlated with the disease grade in knee OA, in agreement with increased p53 [ 28 ].…”
Section: Oa In the Context Of Aging And Metabolic Deregulationmentioning
confidence: 99%
“…As a function of the DNA damage magnitude, p53 may orchestrate homeostatic activities or dysfunctional responses, such as irreversible cell cycle arrest, senescence, or apoptosis [ 27 ] ( Figure 1 ). A recent report explored the correlation of gene and protein expression of cyclin D1, cyclin-dependent kinase 4, and p53 in cartilage derived from a large cohort of patients and healthy controls and showed that cyclin D1 and cyclin-dependent kinase 4 are negatively correlated with the disease grade in knee OA, in agreement with increased p53 [ 28 ].…”
Section: Oa In the Context Of Aging And Metabolic Deregulationmentioning
confidence: 99%
“…Phosphorylation of pRB leads to the release of E2F from pRB binding allowing DNA transcription and cell proliferation to take place, driving the cell cycle from G1 phase into S phase [Tobin et al, ]. A study suggested that cyclin Dl expression is associated with knee osteoarthritis (KOA) [Zhu et al, ]. Besides this study, there is not a lot of current research that investigates the role of cyclin proteins and their relation to the development of OA.…”
mentioning
confidence: 99%
“…MiR-204-5p overexpression has been found to induce downregulation of CCND1 , resulting in differentiation of human MSCs toward adipogenic rather than osteogenic lineage [ 45 ]. Zhu et al also found grade-dependent decrease in mRNA and protein expressions of CCND1 among the knee OA population, compared to healthy controls [ 46 ]. These findings supported our results regarding miR-204-5p regulation in aging bone process, where up-regulated miR-204-5p was postulated to down-regulate SOX11 and be involved in the cell cycle arrest of osteoblasts, leading to clinical observations of increased bone loss among the geriatric population.…”
Section: Discussionmentioning
confidence: 99%